Comparative Analysis of Brain Activation between Healthy Elderly Women and Healthy Adult Women - Lee, Byoungkwon; Han, Dongwook (Journal of Physical Therapy Science, 2011)
[Purpose] This study determined the differences in the brain activation between healthy elderly women (75.89 ± 6.44 years of age) and healthy adult women (22.11 ± 2.04 years). [Subjects] Twenty-seven healthy elderly women who could independent daily living with no history of brain diseases such as stroke or schizophrenia and 27 healthy adult women who are studying at S university in Busan were as participants in this study. [Methods] Examinations used twenty electrodes attached to the head to capture electrical brain signals during brain activated states such as the awaked state and the data were compared between the two groups of women. The AT index is the ratio of theta waves and SMR waves. The AC index is the ratio of alpha waves to low beta waves. The ST index is the ratio of high beta waves to alpha waves. The Mann-Whitney test was conducted to examine changes in EEG. [Results] Fp1, Fp2, Fz, F3, F4, F7, F8, and Pz areas indicate a significantly lower AT index in the healthy elderly women than in the healthy adult women. The Fp1, Fp2, Fz, F3, F4, F7, F8, Pz, P3, and P4 areas all showed a significantly higher AC index in the healthy elderly women, they who also had a significantly higher ST index than the healthy adult women in the Fz, F3, F4, F8, Pz, P3, and P4 areas. [Conclusion] We showed that the brain of the healthy elderly women lacks rest for processing information which is received during eyes open. We also demonstrated the capability of the quantitative EEG in the examination of cognitive impairments.